2022
DOI: 10.1093/eurheartj/ehac544.2341
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) testing in clinical practice: real-life data from a large health-care provider

Abstract: Background Evidence support a causal role of lipoprotein(a) [Lp(a)] in the development of atherosclerotic cardiovascular disease (ASCVD). Novel treatment options are emerging and recent guidelines recommend screening Lp(a) levels at least once during lifetime. However, significant variance exists regarding the incorporation of Lp(a) into patient care. Purpose To investigate patterns of Lp(a) measurement in a large health main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study is part of a retrospective analysis of Lp(a) laboratory tests performed in insured members of the Clalit Health Services (CHS) in Israel, providing inclusive health care for about half of the country's population. The methodology and main features of the overall study population have been previously published [ 9 ]. In short, data on all individuals insured by the CHS in whom Lp(a) testing was performed during the years 2015–2021 were retrieved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a retrospective analysis of Lp(a) laboratory tests performed in insured members of the Clalit Health Services (CHS) in Israel, providing inclusive health care for about half of the country's population. The methodology and main features of the overall study population have been previously published [ 9 ]. In short, data on all individuals insured by the CHS in whom Lp(a) testing was performed during the years 2015–2021 were retrieved.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that this approach may identify people with very high Lp(a) levels >430 nmol/L who may have a lifetime risk of ASCVD equivalent to those with heterozygous familial hypercholesterolemia (HeFH) [ 7 ]. Nevertheless, although the reporting of Lp(a) levels is increasing, it is still measured in only a minority of the population, and data on patients with very high Lp(a) levels in real-life clinical settings are lacking [ 9 ].…”
Section: Introductionmentioning
confidence: 99%